Metal multi-material additive manufacturing : Overcoming barriers to implementation - Clare, A.T.; Woizeschke, P.; Rankouhi, B.; Pfefferkorn, F.E.; Bartels, D.; Schmidt, M.; Wits, W.W. (Elsevier, 2025)
Additive manufacturing has advanced rapidly since its origins in the 1980s. While some processes are now commercially viable, others remain experimental. A key ambition has been to combine multiple materials in a single part, enabling novel properties and overcoming traditional limitations of fabrication and assembly. Multi-material additive manufacturing offers a potential step change across industries, though scaling from lab to industry remains a challenge. This work explores the enabling technologies and science behind metal multi-material additive manufacturing and proposes how the research community can advance these innovations for meaningful industrial impact.